Digital marketing dynamics: Automotive industry strategies - Bermejo Siller, Carmen (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The sector we cover in this research article is the automotive industry, which has been evolving progressively in recent years. To address the object of study, a bibliographic review has been carried out on the latest trends and paradigms in the automotive industry, new forms of consumption and trends in their use. Following the investigation, it has been possible to establish some conclusions in this time of uncertainty in such sector, establishing a series of trends in terms of the most favourable marketing tools to push demand towards stability.